Repurposing functional inhibitors of acid sphingomyelinase (fiasmas): an opportunity against SARS‐CoV‐2 infection?. (1st March 2021) - Le Corre, Pascal; Loas, Gwenolé
Abstract: What is known and objective: Infection by SARS‐CoV‐2, the virus responsible of COVID‐19, is associated with limited treatment options. The purpose of this study was to evaluate the rationale for repurposing functional inhibitors of acid sphingomyelinase (FIASMAs), several of which are approved medicines, for the treatment of SAR‐CoV‐2 infections. Comment: We propose and discuss the FIASMAs' lysosomotropism as a possible explanation for their observed in vitro activities against viruses, and more specifically against infections caused by coronaviruses such as SARS‐CoV‐2. Successful in vitro‐to‐in vivo translation of FIASMAs requires that their pharmacokinetics (dosing regimen and drug‐drug interactions) are matched with viral kinetics. What is new and conclusion: Drug repurposing to ensure rapid patient access to effective treatment has garnered much attention in this era of the COVID‐19 pandemic. The observed lysosomotropic activity of small‐molecule FIASMA compounds suggests that their repurposing as potential drugs against SARS‐CoV‐2 is promising. Abstract : FIASMA are cationic drugs with lipophilic properties that diffuse in the lysosome by passive diffusion and potentially by using ABCB1 transporter located onto the lysosomal membrane. This diffusion increases the intra‐lysosomal pH so that acid sphingomyelinase (ASM) is detached from the inner leaflet of the lysosomal membrane, and is further degraded by proteolysis. Hence, ASM translocation is no longer effective and the formation of lipid rafts on the cell membrane is altered. These membrane modifications impair the different mechanisms of internalization (i.e., fusion and entry) used by viruses such as SARS‐CoV‐2 to penetrate in the cytosol of cells.